STUDENTS’ PERCEPTONS OF GAMIFICATION APPROACH BY USING KAHOOT!: A SURVEY STUDY - Anidya Jihan Savira; Yosephin WL, Maria; Cicik Shopia B, Theresia; Prihadi, Agus (JEE (Journal of English Education), 2024)
Technological innovation has created various learning models and tools that can increase the effectiveness of the learning process. There are a wide variety of learning software and platforms designed to support teachers in their teaching process and help them create a sustainable learning environment. Research has shown that infusion of 'gamification' software can influence and improve student learning outcomes and create a positive learning environment. This article reports a survey study conducted among 32 students from 8D SMP N 36 Semarang who had experience using Kahoot! in the learning process. This study used the closed-ended questionnaire consisting of 10 statements regarding the students' perceptions for gamification approach and the use of Kahoot!. The questionnaire of the Likert Scale consists of 4 (four) alternative points, specifically: Strongly Agree (SA), Agree (A), Disagree (D), and Strongly Disagree (SD). The four-choice scales were used to force respondents to choose one of the points because the points "Neutral" were not available. The results show that almost all participants have positive experiences when participating in learning process that integrates the gamification approach and Kahoot!. The majority of participants reported that they were able to be actively involved in their learning process while using Kahoot! platforms. Adaptive software and platforms like Kahoot! enable students to engage and actively participate in their learning process, and thus provide a more meaningful and rich learning experience.